Hypomagnesaemia As a Mortality Risk Factor in Protein-energy Malnutrition - Karakelleoglu, Cahit; Orbak, Zerrin; Ozturk, Candan Ferai; Kosan, Celalettin (Journal of Health, Population and Nutrition, 2011)
DOI: http://dx.doi.org/10.3329/jhpn.v29i2.7863 J HEALTH POPUL NUTR 2011 Apr;29(2):181-182